Synthesis and Electropolymerization of New Phenylene-Substituted Dipyrridyls: Electrochemical and Spectroscopic Characterization - Karim Diagne Diaw, Abdou; Fall, Modou; Gningue-Sall, Diariatou; Aaron, Jean-Jacques; Yassar, Abderrahim (Asian Journal of Chemistry, 2014)
The present paper sets out the synthesis and electropolymerization process of 1,1'-phenylenedipyrridyl and 1,1'-diphenylenedipyrridyl. These compounds are prepared by Clauson-Kaas methods with 35 or 71 % yield and characterized. UV-visible electronic absorption spectra and electrochemical methods were used to examine the effects of the electronic p-system extension in 1,1'-phenylenedipyrridyl and 1,1'-diphenylenedipyrridyl structures on the monomer properties relative to N-phenylpyrrole. Also, 1,1'-phenylenedipyrridyl and 1,1'-diphenylenedipyrridyl were electropolymerized on platinum electrode by anodic oxidation in 0.1 M tetrabutylammonium hexafluorophosphate (Bu4NPF6) acetonitrile or dichloromethane solutions and characterized by electrochemical and spectroscopic techniques. The electronic p-system extension effects on the poly(1,1'-phenylenedipyrridyl) physico-chemical properties and structure were investigated by cyclic voltammetry, FT-IR, UV-visible and XPS spectroscopy and scanning electron microscopy (SEM). Cyclic voltammetry of the poly(1,1'-phenylenedipyrridyl) films indicated a good redox behaviour and an improvement of the electrochemical properties. FT-IR spectral studies indicated a linear structure of this polymer with 2, 5 coupling on the pyrrole ring. SEM analysis showed that polymer film morphology changed between the oxidized and reduced states. The solid-state UV-visible spectra of the poly(1,1'-phenylenedipyrridyl) films on ITO were characterized by a significant red-shift of the absorption maximum, as compared to poly(1,1'-phenylenedipyrridyl) film. Moreover, the very low amount of poly(1,1'-diphenylenedipyrridyl) film obtained during the electropolymerization process and electrochemical studies of electrosynthesized poly(1,1'-diphenylenedipyrridyl) showed that the polymer properties modulated by extension of the monomer electronic p-system can be limited by steric effects.